Sustainability Reporting, Profitability, Firm Value, and Good Corporate Governance: Systematic Literature Review - Ade Sandra Dewi; Agriyanti Komalasari; Fitra Dharma (Penerbit Goodwood, 2025)
Purpose: This study examines how sustainability reporting, profitability, and Good Corporate Governance (GCG) collectively influence firm value, addressing fragmented evidence across contexts and theories, and providing an integrated synthesis of prior literature to clarify inconsistencies, strengthen theoretical explanations, and identify gaps for future empirical research. Methodology: A Systematic Literature Review (SLR) combined with thematic and bibliometric-style mapping was conducted on 71 studies (1973–2026). Studies were selected using an adapted identification–screening–eligibility–inclusion protocol and analyzed through manual co-occurrence coding of key constructs. Results: Five thematic clusters emerged: sustainability/ESG disclosure, firm value and market performance, profitability, corporate governance, and theoretical foundations (Signaling, Agency, Legitimacy). Findings indicate generally positive but context-dependent relationships among sustainability reporting, profitability, and firm value, with GCG frequently strengthening these effects. However, theories are often applied in isolation rather than integrated. Conclusions: An integrated conceptual framework is required to better explain the sustainability–profitability–governance–value nexus, particularly in emerging markets. Limitations: The review is limited by reliance on secondary studies and uneven geographic and sectoral representation, with limited evidence from tourism firms in emerging economies. Contributions: This study synthesizes fragmented literature, proposes an integrated framework, and identifies key gaps for future panel-data and sector-specific research.